Non-Hodgkin's lymphoma of the maxilla: A rare case report and review - Rajarshi Banerjee; Arup K Ghosh; Mayukh Misra; Arpita Kabiraj (Wolters Kluwer Medknow Publications, 2017)
Non-Hodgkin's lymphomas (NHLs) embody a diverse group of malignancies that originate from the lymphoid system. NHL often exhibit in an extranodal pattern, pertaining to the head and neck region. Intraoral sites are much less frequent, accounting for approximately 3.5% of all oral malignancies. Although the exact cause of NHL still remains inconspicuous, however, research has focused on some factors that may contribute to the development of lymphoma, including genetic factors, impaired immune system and viruses, such as HIV or EBV. Clinically, the bony lesion may present as localized or diffuse swelling, with low-grade pain, sweating, unexplained weight loss, fever, etc. Radiographically, these lesions resemble osteomyelitis or other malignancies creating a diagnostic dilemma. Microscopically, diffused lymphomas consist of large tumor cells with large nuclei that are more than twice the size of lymphocytes which may either exhibit centroblastic or immunoblastic features. Here, we report a rare case of NHL affecting the jaws of a 60-year-old male patient.